Seismic Vulnerability Microzonation Based on Dominant Frequency and Amplification Using the HVSR Method in Wedi, Changewaro (Klaten) and Gendangsari (Yogyakarta) - Desi Mustami Limayukha, Desi Mustami Limayukha; Adhi, Mochamad Aryono Adhi; Wibowo, Nugroho Budi; Bilqis El Farsiyyi, Billqis El Farsiyyi; Elsa Fadlika Widyantari, Elsa Fadlika Widyantari; Ilqia Rahma, Ilqia Rahma; Rahmania Sofyana Ulya, Rahmania Sofyana Ulya (Rekayasa, 2022)
The Yogyakarta region is prone to frequent earthquakes, highlighting the need for seismic vulnerability assessment and micro zonation analysis. This study aimed to evaluate the area's seismic vulnerability by utilizing microtremor methods to estimate dominant frequency, amplification, seismic vulnerability index, and shear wave velocity. Microtremor points were analyzed using the Horizontal Vertical Spectral Ratio method, with data processed through Geopsy software to obtain f0, A0, and H/V curves. The H/V curve was further inverted using Dinver software to derive ellipticity curves, ground profiles, and Kg values. The results revealed that the dominant frequency values ranged from 0.668 Hz to 18.271 Hz, with higher values prevalent. The soil types in the area were classified as type IV and type I, primarily consisting of older, hard sandy rocks and gravels. Amplification values ranged from 1.03 to 8.36, indicating low amplification levels and placing the area in zone 1. Kg values varied from 0.066 to 15.07 s²/cm, suggesting moderate seismic vulnerability. If an earthquake occurs, the region would experience shaking, though damage would be moderate. Vs30 values ranged from 179.64 m/s to 681.82 m/s, categorizing the soil as hard, dense, soft, or medium.